Trauma, Romance, and the Diasporic Memory Keepers of the Holodomor in Erin Litteken’s The Memory Keeper of Kyiv - Mateusz Świetlicki (European Journal of American Studies)
A few months after its publication in North America, Erin Litteken’s bestselling historical novel The Memory Keeper of Kyiv (2022) has already been translated into fourteen languages. Thus, it is plausible that for many readers the novel will be the first encounter with the complex topic of the Great Famine of 1932-1933 in Soviet Ukraine. This article examines the narrative techniques used in The Memory Keeper of Kyiv and demonstrates that the combination of romance and historical fiction enables Litteken not only to introduce readers possessing little to no knowledge of Ukrainian history to the Holodomor but also show the links between Ukraine and North America and those between the present and past genocides in Ukraine. After a brief introduction to the historical context of the Holodomor, the article shows that by using two timelines—one set in 2004 and the other during the Great Famine—Litteken showcases the intergenerational and transcultural character of individual and collective trauma. Finally, it points to the fact that the novel’s present-day protagonist reflects the belated recognition of the Holodomor among the assimilated representatives of the Ukrainian American diaspora and their alleged responsibility to prevent the memory of the Famine from falling into oblivion.